2021
DOI: 10.1364/oe.432265
|View full text |Cite
|
Sign up to set email alerts
|

Widely stretchable soliton crystals in a passively mode-locked fiber laser

Abstract: We present the first direct demonstration of a new type of stable and extremely elastic soliton crystals, the bond length and bond strength of which can be individually controlled in a wide range. The stretching and compressing can be repeated many times, conserving the overall structure by incorporating a highly asymmetric tunable Mach-Zehnder interferometer into a specially designed passively mode-locked fiber laser. The temporal structure and dynamics of the generated soliton crystals were measured using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
5
0
4
Order By: Relevance
“…The scheme is based on a specially designed Er-doped modelocked fiber laser that generates bunches and trains of pulses of different amplitudes with controllable temporal spacing between the pulses (SM laser). The laser schematic and its operation principle are described in detail in [21]. In brief, mode-locking is achieved by a nonlinear amplifying loop mirror used as a saturable absorber, and tuning of the pulse-topulse temporal spacing is achieved by an adjustable unbalanced Mach-Zehnder interferometer (MZI) installed inside the laser cavity.…”
Section: Experimental Schemementioning
confidence: 99%
See 1 more Smart Citation
“…The scheme is based on a specially designed Er-doped modelocked fiber laser that generates bunches and trains of pulses of different amplitudes with controllable temporal spacing between the pulses (SM laser). The laser schematic and its operation principle are described in detail in [21]. In brief, mode-locking is achieved by a nonlinear amplifying loop mirror used as a saturable absorber, and tuning of the pulse-topulse temporal spacing is achieved by an adjustable unbalanced Mach-Zehnder interferometer (MZI) installed inside the laser cavity.…”
Section: Experimental Schemementioning
confidence: 99%
“…One way to get more control over the SC generation is to provide a more flexible pump pulse source. In this work we demonstrate the application of a novel recently developed pulse source based on a soliton-crystal mode-locked laser [21] for SC generation. It provides extremely wide tunability of the effective repetition rate up to sub-THz and the possibility of generating heterogeneous pulse sequences, where pulses of high and low amplitudes can interleave.…”
Section: Introductionmentioning
confidence: 99%
“…[4,15,37,[39][40][41] Further, interactions of multiple solitons create "supramolecular" structures and soliton crystals were also revealed in theoretical and experimental studies. [9,16,25,35,37,42] An essential issue is how far the analogy of SMs to real chemical molecules can extend. [16,37] A limitation is that, in most cases, mode-locked lasers generate identical optical solitons, whose parameters are uniquely selected by the gain competition effect and resulting energy quantization.…”
Section: Introductionmentioning
confidence: 99%
“…The longrange interactions are mediated by various mechanisms such as continuous wave (CW) components, dispersive wave mediation [17], gain depletion and recovery [18,19], as well as fiber acoustic effects [20]. In addition, Andrianov et al reported a new mechanism of long-range pulse-to-pulse interaction in a mode-locked fiber laser with an unbalanced Mach-Zehnder interferometer, in which elastic soliton crystals were produced [21,22]. Different soliton interaction mechanisms could coexist in the fiber laser cavities.…”
Section: Introductionmentioning
confidence: 99%